2008
DOI: 10.1007/s12272-001-1234-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and hypnotic activities of N-Cbz-α-aminoglutarimidooxy carboxylate derivatives

Abstract: Typical hypnotic drugs, such as barbitals and glutethimide, have a cyclic imide (-CO-NH-CO-) moiety. The N-Cbz-alpha-aminoglutarimidooxy carboxylate derivatives, which we previously showed exhibit moderate anticonvulsant activities, also have a cyclic imide (-CO-N-CO-) moiety. This structural similarity prompted us to examine the hypnotic activities of the N-Cbz-alpha-aminoglutarimidooxy carboxylate derivatives, and we describe their moderate hypnotic activities here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Cyclic imide derivatives exhibiting anti-inflammatory (Abdel-Aziz et al, 2011;Al-suwaidan et al, 2013), antibacterial (Kumari and Singh, 2014), antinociceptive (de oliveira et al, 2012), anticonvulsant (Sharma et al, 2008a, b), anticancer (Machado et al, 2011;El-Azab et al, 2013), hypolipidemic (El-Zahabi et al, 2012 and hypnotic (Byun et al, 2008) activities are well reported in literature. Cyclic imide derivatives are also inhibitors of amino peptidase N (Li et al, 2010) and Mycobacterium tuberculosis protein tyrosine phosphatase B .…”
Section: Introductionmentioning
confidence: 98%
“…Cyclic imide derivatives exhibiting anti-inflammatory (Abdel-Aziz et al, 2011;Al-suwaidan et al, 2013), antibacterial (Kumari and Singh, 2014), antinociceptive (de oliveira et al, 2012), anticonvulsant (Sharma et al, 2008a, b), anticancer (Machado et al, 2011;El-Azab et al, 2013), hypolipidemic (El-Zahabi et al, 2012 and hypnotic (Byun et al, 2008) activities are well reported in literature. Cyclic imide derivatives are also inhibitors of amino peptidase N (Li et al, 2010) and Mycobacterium tuberculosis protein tyrosine phosphatase B .…”
Section: Introductionmentioning
confidence: 98%